P037 Patterns of Care Among Patients Treated With Ustekinumab for Crohn's Disease: Results From a Chart Review. (December 2019) - Ruetsch, Charles; Davis, Tigwa; Clerie, Jennifer; Obando, Camilo; Izanec, James; Muser, Erik
Abstract : BACKGROUND: Crohn's Disease (CD) is a chronic, progressive disease that causes severe and debilitating symptoms often leading to hospitalizations and surgeries. Biologic therapy can treat the underlying pathology, but treatment non-response is common. In 2016, the FDA approved ustekinumab for the treatment of adult patients with moderately to severely active CD who have failed or were intolerant to conventional therapy or failed or were intolerant to treatment with one or more TNF blockers. The study objective was to use chart data to characterize CD patients starting ustekinumab. METHODS: Of the medical charts for 109 adult CD patients who initiated ustekinumab therapy (index), 100 charts (92%) for patients who remained on UST therapy at six months were analyzed. Variables extracted from charts included patient demographics, CD-related complications, CD medication use, disease duration, and lab values. The 3 measurement periods were: 1) historical (up to 3 years prior to index); 2) pre-index period (6 months prior to index) and 3) post-index period (6 months following index dose). RESULTS: The study sample was mostly female (65%) and Caucasian (58%) with a mean age of 42.2 ± 14.9 yrs and a disease duration of 9.6 ± 10.5 yrs. Of the 100 patients, 82% were bio-experienced, including 45 who had already failed at least two biologics prior to starting ustekinumab. Adalimumab was the most recent biologic used in 49% of patients, followed by vedolizumab (21%), infliximab (17.5%), and certolizumab (12.3%). The most common reasons for switching to ustekinumab were secondary loss of response (48%), followed by primary non-response (15%), and side effects (13%). During the pre-index period, 18 (17%) reported a CD-related complication (e.g., fistula, obstruction, anemia, etc.) and these complications resolved in 16 of 18 patients (89%) during the treatment period. In the post-index period, only 50% of patients had at least one lab test in the chart and only 2% underwent a colonoscopy. Over the treatment period, steroid used decreased by 61% from 23% of the study population pre-index to 9% post-index ( P < 0.01). CONCLUSION(S): Three-fourths of patients who started ustekinumab had previously failed other biologic therapies, and over 90% remained on ustekinumab for at least the six months after initiating treatment. During this time, most patients had resolution of their CD-related complications and most patients on steroids were able to discontinue them.